Microscale techniques for the organic laboratory - Mayo, Dana W. (John Wiley & Sons, Inc., 2001)
Microscale programs have been shown to be a superior style of laboratory instruction--safer, cheaper, and better pedagogically. This text gives the instructor the opportunity to mix miniaturized instruction with conventional-scale work by providing detailed descriptions of microscale techniques.